Use of Endoscopic Ultrasound with Bronchoscope-Guided Fine-Needle Aspiration (EUS-B-FNA) in Pediatric Cases - Xiaowei Chen; Xiaofen Tao; Shuxian Li; Hujun Wu; Fang Jin; Lei Wu (Children)
The intricate airway anatomy and poorly understood etiology of pediatric conditions render the diagnosis of mediastinal disorders particularly challenging. Traditional diagnostic methods, such as mediastinoscopy and thoracotomy, carry high risks and are often impractical in children. Endoscopic ultrasound with bronchoscope-guided fine-needle aspiration (EUS-B-FNA) enables a minimally invasive, esophageal route to mediastinal lesions, providing a diagnostic approach that is new to pediatrics compared with conventional techniques. We review the technical characteristics, clinical benefits, and prospective role of EUS-B-FNA in pediatric diagnostic investigation. We also review the clinical applications of EUS-B-FNA to date and aim to promote its use as a novel adjunct for the evaluation of complex mediastinal pathology in pediatric medicine.